2013
DOI: 10.1016/j.nimb.2013.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Operational limit of a planar DC magnetron cluster source due to target erosion

Abstract: The binary collision-based two dimensional SDTrimSP-2D model has been used to simulate the erosion process of a Cu target and its influence on the operational limit of a planar DC magnetron nanocluster source. The density of free metal atoms in the aggregation region influences the cluster formation and cluster intensity during the target lifetime. The density of the free metal atoms in the aggregation region can only be predicted by taking into account (i) the angular distribution of the sputtered flux from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All nanoparticles were grown using a 2 inches diameter full face erosion (FFE) magnetron (Nano4Energy SL) fitted into a standard gas aggregation source (GAS) (Oxford Applied Research Ltd.). The FFE magnetron that is made of rotating magnets generates a much more uniform erosion of the sputtering target and extends its lifetime, while it also eliminates the well-known fluctuations of the NP generation caused by the racetrack formation in standard magnetrons. , Hence, a stable generation of NPs could be achieved for long periods of time. The magnetron was positioned at its longest aggregation distance (i.e., magnetron head at 100 mm from exit slit of aggregation zone) and a stable flux of argon (80 sccm) gas was injected through a mass flow controller at the back side of the aggregation zone.…”
Section: Methodsmentioning
confidence: 99%
“…All nanoparticles were grown using a 2 inches diameter full face erosion (FFE) magnetron (Nano4Energy SL) fitted into a standard gas aggregation source (GAS) (Oxford Applied Research Ltd.). The FFE magnetron that is made of rotating magnets generates a much more uniform erosion of the sputtering target and extends its lifetime, while it also eliminates the well-known fluctuations of the NP generation caused by the racetrack formation in standard magnetrons. , Hence, a stable generation of NPs could be achieved for long periods of time. The magnetron was positioned at its longest aggregation distance (i.e., magnetron head at 100 mm from exit slit of aggregation zone) and a stable flux of argon (80 sccm) gas was injected through a mass flow controller at the back side of the aggregation zone.…”
Section: Methodsmentioning
confidence: 99%
“…The race track is well-known to form on the target surface [18] and its formation has been extensively reported in the literature even in SGAS [19,20]. In their works, Hippler et al have analyzed and discussed the effect of the race track formation on the generation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In their works, Hippler et al have analyzed and discussed the effect of the race track formation on the generation of nanoparticles. In particular, they have clearly shown that the formation of the race track has an influence on the nanoparticle size and synthesis rate [19,20]. Note that the synthesis rate is referred to the number of nanoparticles that are formed into the aggregation zone (by unit time) and the deposition rate to the number of nanoparticles that are collected (by unit time and surface) outside the aggregation zone (typically on a flat surface).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the erosion profile of the target can affect the NPs synthesis in a GAS. [51] The deposition characteristics of the gas-phase synthesis of NPs, in general, are varying throughout the target lifetime, [49][50][51] which, in particular, is a challenge to be overcome in the case of multicomponent targets. Thus, a reliable in operando diagnostic approach is in high demand to satisfy the necessity of a precise control of the NP composition.…”
mentioning
confidence: 99%
“…[49,50] Furthermore, the target erosion profile influences the NPs synthesis and limits the working window in which NPs can be produced. [51] Due to these target history effects, a precise prediction of NP composition just based on operation pressure, which was suggested in an earlier report, [48] is impossible for long-term use of a multicomponent target. To account for the immense significance of precise control over NP properties for application purposes, a diagnostic approach to control the NP composition is presented.…”
mentioning
confidence: 99%